Economic Growth and Environmental Degradation: A Panel Data Analysis of Carbon Emissions and GDP Across Developing Countries - Ayu Trisanti; Oslan Juliana Simbolon (Cv. Data Sinergi Digital, 2025)
The relationship between economic growth and environmental degradation remains a critical issue for developing countries that seek to sustain economic expansion while reducing carbon emissions. Grounded in the Environmental Kuznets Curve (EKC) hypothesis, this article examines the relationship between carbon dioxide (CO₂) emissions and gross domestic product (GDP) per capita across 65 developing countries during 2000-2022. The empirical analysis applies panel data estimation techniques, including Fixed Effects, Random Effects, the Hausman specification test, and System Generalized Method of Moments (System GMM) to address potential endogeneity. Energy consumption, renewable energy share, foreign direct investment (FDI), and trade openness are included as control variables. The findings support the EKC hypothesis. GDP per capita has a positive and significant effect on CO₂ emissions, while the squared term of GDP per capita has a negative and significant effect, confirming an inverted U-shaped relationship. The estimated turning point of approximately US8,742 per capita indicates that many developing countries remain in the growth phase where emissions continue to rise. Energy consumption is the strongest positive driver of emissions, whereas renewable energy share significantly reduces environmental degradation. FDI shows a positive but statistically insignificant effect, while trade openness significantly increases emissions. System GMM estimation confirms the robustness of the results after controlling for endogeneity and emissions persistence. These findings highlight the need for renewable energy transition, stronger environmental governance, and trade-investment policies that support green growth in developing economies.